THE MEDIATING ROLE OF SELF-EXPERIENCE IN THE INFLUENCE OF PRINCIPAL LEADERSHIP AND PROFESSIONAL DEVELOPMENT ON TEACHER COMPETENCE: PLS-SEM ANALYSIS - Annisa Nur Faradila; Rihab Wit Daryono (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2024)
In education, teacher competence greatly determines the quality of the learning process and outcomes, while principal leadership and professional development are considered important factors that influence these competencies. However, there is a gap in understanding how teacher self-experience can act as a bridge in the influence of both factors on teacher competence, especially in Islamic educational environments such as Madrasah Tsanawiyah. This study examines and analyzes the influence of principal leadership and professional development on teacher competence through self-experience mediation. The research method used is a quantitative approach with a PLS-SEM analysis model. The research sample involved 58 teachers from MTsN 9 Magetan and MTsN 6 Madiun, selected through proportional random sampling techniques. Data were collected using questionnaires and analyzed using path analysis techniques and direct and indirect effects hypothesis testing. The results showed that professional development positively and significantly influenced self-experience, while self-experience significantly influenced teacher competence. However, the influence of principal leadership on self-experience and teacher competence was not substantial. Self-experience was also shown to mediate the positive influence of principal leadership and professional development on teacher competence, although not significantly on the influence of leadership. This conclusion emphasizes the importance of self-experience as a mediator that can strengthen the influence of professional development on teacher competence. Recommendations from this study suggest improving teacher professional development programs and leadership training that emphasize personal experience and reflection.